Association of COVID-19 pandemic and depression occurrence in university students worldwide - Gilandoust, Azin; Momeni Torkaman, Fariba (Journal of Biological Studies, 2022)
Many studies have shown that the Covid-19 pandemic is followed by psychological problems in students; However, the exact effects of the Covid-19 pandemic on student depression are not entirely clear. Accordingly, the present review study examines the relationship between the Covid-19 pandemic and the incidence of depression in students worldwide. During this library and documentary research, 95 sources including books, articles and online references were examined. The inclusion criteria were based on viral infectious diseases, Covid-19 and the incidence of depressive mental disorder. The validity of the sources was evaluated according to the indexes and the use of validation sites, and after ensuring their validity, information was collected. Finally, the information was categorized using descriptive statistics. The Covid-19 pandemic in different countries has had a significant effect on the incidence of depression in students, however, the severity of mental disorders associated with the Covid-19 pandemic in underdeveloped countries is significantly higher than in developed countries. The occurrence of psychological disorders during the corona pandemic period is completely different in students according to the length of the quarantine period, social restrictions, the field of study, age and gender, and economic and social level of students. The results of this study showed that the corona pandemic has been significantly effective in the incidence of depression in students worldwide, and therefore it is very important and vital to consider counselling and psychological support programs for students in universities.